Cultura tributaria y su efecto en la recaudación del GAD El Empalme período 2021-2022 - Muñoz Intriago, Diana Cecibel (2023)
In the GAD of the El Empalme canton, some inconveniences are evident due to the low level of collections, affecting the budget items that must be used in order to be reverted to works for the canton, but that cannot be fully executed, due to the lack of tax culture of citizens. The objective of the present investigation was to determine the incidence of non-compliance with tax obligations in the efficiency of tax collection of the GAD of the El Empalme canton. As part of the theoretical framework of the investigation, the related conceptual, theoretical and legal foundation was elaborated. to the research topic. Exploratory and descriptive research was used; the inductive, deductive and analytical method; As well as the technique of the interview with the financial director, the survey was applied to a sample of taxpayers of the Municipal GAD of El Empalme. Among the results obtained, 68% indicated that they have rarely been made aware of their rights and tax obligations as taxpayers, 52% answered that they are rarely informed about the destination of tax and non-tax income collected by the El Empalme Municipal GAD and 52% stated that they almost always consider it a normal attitude for taxpayers not to pay their taxes. It is concluded that there are worrying levels of tax evasion in the payment of taxes by citizens, which is due to a poor tax culture among the economically active population. It is necessary to implement a permanent tax education program, which contributes to compliance with the collections of the GAD El Empalme, which must have the purpose of training and motivating taxpayers for the cancellation of their tax obligations, promoting the tax culture among taxpayers, and improve the predisposition of the citizens of this canton.